Influence of technological factors on physical and mechanical properties of laminated prints - Havenko, Svetlana (Strojniški vestnik, 2008)
Research of qualitative parameters of lamination at different technological modes for different papers is carried out. Influence of temperature and speed of print lamination with an OPP film on the quality of laminates is considered. A mathematical model describing the strength and curling of a laminate depending on the regime factors of the process has been developed. Optimization of the technological process has been carried out.
Keywords: tehnološki postopki; optimiranje; polipropilen; papir; laminiranje